Islamic political economy and sustainable social development policies: an analytical study - Adam Sa'ad, Auwal; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina (2019)
In the contemporary economic societies, the world is witnessing a vibrant transformation from vague economy to an economic reality; the emergence of the Islamic economic system has been in trial for almost five decades. The current achievements of Islamic banking and finance industry were believed to have realized through the accelerated efforts of governments across the globe and their enthusiasm and compassion towards the development of Islamic Financial industry. It was argued that the Islamic economic system has all the potentials to becoming the world prevailing system due its reliance on justice, fairness, socio-economic reality and sustainable development. This might be achieved through the realization of the Islamic social policies and its possible implementations across the globe. The Islamic political economy has all in need to sharpen the socio-economic development of the contemporary societies towards a sustainable economic development around the world and has the strong mechanisms for social support and achievements.